Community Participation in the Adiwiyata Program for Strengthening Character Education of MAN Students in South Kalimantan - Z, Eddy Khairani; Hanafiah, Hanafiah; Iriantara, Yosal; Sauri, HR Supyan (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
This study aimed to identify the implementation of adiwiyata policies as an effort to realize environmental education in madrasas. It is to realize environmental education effectively and efficiently. The method is case study method at MAN 1 Tapin and MAN 2 Tapin to find out how to plan, implement, organize, evaluate, support and inhibit factors as well as solutions and future improvement efforts in the Adiwiyata program to strengthen character education of MAN students. The results of this study were the community participation in the Adiwiyata program for strengthening character education for MAN 1 Tapin and MAN 2 Tapin students was carried out with reference to applicable regulations and guidelines, but it had not performed the efforts to strengthen character and the level of community participation.